Enhancing global supply chain sustainability : a comprehensive risk perception analysis - Camões, Afonso Tiago Pinto Nunes da Silva (2024)
At a time when sustainability imperatives are reshaping global supply chains, this thesis ventures into the evolving landscape of sustainable supply chain management (SSCM), focusing on the risk perception and management among Europe’s leading revenue-generating companies in 2022. By navigating a complex array of sustainability risks, companies must adapt a pivotal role in efficiently control the multifaceted nature of these risks, overcoming challenges and pressures from both internal and external spheres. This study employs a mixed-method approach to analyse the plethora of nuances regarding risk perception variability across industries, influenced by geopolitical and industry-specific dynamics, while bridging the gap between theoretical concepts and real-word practices. To answer the research question “How do companies perceive risks in sustainable supply chain management?”, this thesis showcases that European companies articulate and manage sustainability risks differently intra-industry, across countries, and inter-industry, reflecting on the importance of industry wise and geopolitical pressures on risk management strategies. This thesis delineates the diversity of sustainability risk perception within global supply chains of Europe's top revenue-generating companies, laying the groundwork for future research and practice in enhancing SSCM amid the pressing challenges of the present.